2017
DOI: 10.1097/jcn.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms Suggestive of Acute Coronary Syndrome

Abstract: Women and men evaluated for ACS reported similar rates of chest pain but differed on other classic symptoms. These findings suggest that women and men should be counseled that ACS is not always accompanied by chest pain and multiple symptoms may occur simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
0
27
0
3
Order By: Relevance
“…Patients with ACS experience a variety of symptoms on the onset of the coronary event (Canto, Goldberg, & Sopko, 2012a). Although chest pain or discomfort are the most common symptoms of ACS, patients experience a wide variety of other symptoms, such as fatigue, shortness of breath, nausea, or back pain (DeVon et al, 2017;Wikman et al, 2012) and these symptoms are linked to clinical outcomes, such as the mortality rate or quality of life (El-Menyar et al, 2011;Spertus et al, 2004). Most studies have focused on the symptoms among patients with ACS during acute cardiac events and symptom differences according to age and sex (Canto et al, 2012b;DeVon et al, 2017;Fennessy et al, 2010;Rosenfeld et al, 2015).…”
Section: Factors That Influence Health-related Quality Of Life In Patmentioning
confidence: 99%
“…Patients with ACS experience a variety of symptoms on the onset of the coronary event (Canto, Goldberg, & Sopko, 2012a). Although chest pain or discomfort are the most common symptoms of ACS, patients experience a wide variety of other symptoms, such as fatigue, shortness of breath, nausea, or back pain (DeVon et al, 2017;Wikman et al, 2012) and these symptoms are linked to clinical outcomes, such as the mortality rate or quality of life (El-Menyar et al, 2011;Spertus et al, 2004). Most studies have focused on the symptoms among patients with ACS during acute cardiac events and symptom differences according to age and sex (Canto et al, 2012b;DeVon et al, 2017;Fennessy et al, 2010;Rosenfeld et al, 2015).…”
Section: Factors That Influence Health-related Quality Of Life In Patmentioning
confidence: 99%
“…9 Furthermore, findings from a multicenter study of 1064 patients admitted to the emergency department for symptoms suggestive of ACS revealed that women with ACS were less likely than men to report chest pain as their chief complaint. 10 Studies have also shown that women are more likely to report a greater number of symptoms and more diverse symptoms at presentation. 916 In fact women are more likely than men to have back/neck/jaw or arm pain, shortness of breath, cough, or paroxysmal nocturnal dyspnea, nausea/vomiting/indigestion or lack of appetite, weakness, fatigue, dizziness, syncope, palpitations, and/or a sense of dread with their ACS event.…”
Section: Introductionmentioning
confidence: 99%
“…11 The investigation conforms with the principles outlined in the Declaration of Helsinki. 12 The Institutional Review Board (IRB) from the sponsoring institution and each clinical data collection site gave approval for the study prior to launch.…”
Section: Methodsmentioning
confidence: 96%